TELAAH TAFSIR SYI`AH: Karakteristik dan Metodologi Tafsir Al-Mizan karya Allamah Thabathaba’i dan Contoh Penerapannya dalam Hukum Keluarga - Eva Nur Hopipah; Mohamad Athoilah; Mohamad Sar'an (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2023)
Al-Qur'an is the revelation of Allah revealed to the Prophet Muhammad, which to understand it requires in-depth knowledge from various aspects, for the benefit of human life in everyday life. Therefore, it is necessary to have the Science of Tafsir to understand it and not everyone is able to become a commentator, only special people are able to understand the Qur'an in its entirety. Because human thoughts are different, there are various interpretations of the Qur'an that can be used as guidelines for believing and living. One of the most popular interpretations is the Shi'ite Tafsir by Allamah Thabhathabha'i. He is the author of the commentary of al-Mizan. Some interesting things can be found in this commentary for discussion in the interpretation that is spread not only among Shia Muslims, but also Sunni Muslims. Several factors because this interpretation can also be accepted by Sunni Muslims because the interpretation prioritizes the use of bi al-ma'tsur sources, which means that the interpretation really comes from the Qur'an. The research method used is a research library or library research that dissects the biography of the mufassir, the characteristics and methodology of his interpretation, to what are the advantages and disadvantages of Al-Mizan's interpretation.